Peran Humas dalam Menjalin Kemitraan dengan Pers untuk Peningkatan Publisitas Sekolah di SMPN 12 Jember - Sapna Indah Nia; Nuraida Edlin Hafizah; Siti Hofsatul Karimah; Yunda Nurul Millati Hoiriyah; Rofiq Hidayat (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the role of Public Relations in establishing partnerships with the press to increase publicity at SMPN 12 Jember. The background of this study is influenced by the importance of positive media publications in building a school's reputation and competitiveness amidst intense competition among educational institutions. The research method used is a qualitative case study approach, involving in-depth interviews, participant observation, and documentation studies of public relations staff and media partners. The results show that the role of public relations has evolved from an administrative function to a strategic spearhead that manages two-way communication, fosters relationships, and builds reputation. The strategies implemented include the use of convergent media, by combining traditional media (such as school magazines and brochures) with digital media (such as websites, Instagram, and YouTube) to expand the reach of messages. In addition, adaptations to local culture, such as the use of polite Javanese language and a family-like approach, have proven effective in building public trust. This study also emphasizes the importance of systematic and participatory evaluation to improve program effectiveness. The implications of this study suggest that schools design measurable and contextual public relations strategies with local values ​​to increase the school's visibility and positive image.